Creativity of Driving Teachers in Developing Learning Interests of Class V Elementary School Students - Nurlaeli; Febriani, Tiara; Syarifuddin, Ahmad; Hamzah, Amir; Tastin (Universitas Pendidikan Ganesha, 2023)
The curriculum in Indonesia has changed according to the times. The government offers the concept of the Merdeka Learning Merdeka Curriculum, intending to adjust to the talents and interests of students. The government held a driving teacher training program requiring teachers to be more creative in learning. This study aims to analyze teachers' characteristics, student interests in learning, and the influence of the creativity of driving teachers in developing students' learning interests. This type of research is quasi-experimental quantitative. The population in this study were all fifth-grade elementary school students consisting of 63 students. Data collection techniques with questionnaires, interviews and documentation. The data analysis technique used is simple linear regression. Research using validity tests, reliability tests, and hypothesis testing. The research results from the driving teacher's creativity by doing ice breaking. Change the classroom atmosphere, use various media and methods, and create various learning materials and media. Students' interest in learning is in the form of liking doing assignments, being enthusiastic about learning, enjoying working with teams, liking practical learning activities, being active and online to give opinions in class. The creativity of the driving teacher influences in developing students' learning interests. It was concluded that the driving teacher's creativity significantly affected the developing students' learning interests. And create various learning materials and media. Students' interest in learning is in the form of liking doing assignments, being enthusiastic about learning, enjoying working with teams, liking practical learning activities, being active and online to give opinions in class. The creativity of the driving teacher influences in developing students' learning interests. It was concluded that the driving teacher's creativity significantly affected the developing students' learning interests. And create various learning materials and media. Students' interest in learning is in the form of liking doing assignments, being enthusiastic about learning, enjoying working with teams, liking practical learning activities, being active and online to give opinions in class. The creativity of the driving teacher influences in developing students' learning interests.